1985
DOI: 10.1007/bf00295164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral cadmium administration to female rats during pregnancy on zinc, copper, and iron content in placenta, foetal liver, kidney, intestine, and brain

Abstract: Cadmium chloride was administered in drinking water at a concentration of 50 ppm cadmium to female rats for 20 days of gestation. The foetuses were then removed from the uteri of the dams. Gestational exposure to oral cadmium resulted in decreased zinc, copper, iron, metallothionein, and thionein-bound zinc content in foetal liver as well as in reduced copper content in placenta and foetal intestine, brain and kidney. Subcellular fractionation of the foetal liver revealed decreased nuclear and cytoplasmic zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
2
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 24 publications
4
14
2
2
Order By: Relevance
“…In contrast to our observations, these authors observed deficits in the birth weight and growth of animals prenatally exposed to Cd, the latter being effects that could be responsible for a delayed sensorimotor development (Smart and Dobbing, 1971). Evidence from previous studies indicates that the oral administration of Cd results in a reduced absorption of trace elements such as Ca, Zn and Fe (Pond and Walker, 1975;Sowa and Steibert, 1985;Baranski, 1987). In this work, the Cd subcutaneously administered during organogenesis could therefore be responsible for alterations in the normal development of sensorimotor reflexes and motor coordination of the offspring which are reflected in the observed maturation deficits of the righting reflex and in the cliff aversion.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our observations, these authors observed deficits in the birth weight and growth of animals prenatally exposed to Cd, the latter being effects that could be responsible for a delayed sensorimotor development (Smart and Dobbing, 1971). Evidence from previous studies indicates that the oral administration of Cd results in a reduced absorption of trace elements such as Ca, Zn and Fe (Pond and Walker, 1975;Sowa and Steibert, 1985;Baranski, 1987). In this work, the Cd subcutaneously administered during organogenesis could therefore be responsible for alterations in the normal development of sensorimotor reflexes and motor coordination of the offspring which are reflected in the observed maturation deficits of the righting reflex and in the cliff aversion.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, our results show that Cd was accumulated in the placenta and in fetal liver but it was not detected in the fetal testis of Cd exposed-animals. These results suggest that placenta could deter most of Cd to passing from dams to fetus [32][33][34]. Importantly, exposure to Cd in utero did not impair fetus growth since the fetal weights and the craniocaudal length at the end of gestation (GD20) of the control and Cd group were not statistically different.…”
Section: Discussionmentioning
confidence: 77%
“…Gestational exposure to oral cadmium resulted in decreased zinc, copper, iron, and metallothionein (MT) content in fetal liver as well as in reduced copper content in the placenta and fetal intestine (Sowa et al, 1982;Steibert et al, 1984;Sowa and Steibert, 1985).…”
Section: Introductionmentioning
confidence: 99%